The challenging diagnosis of food protein-induced enterocolitis syndrome: A case report series - Zhao, Caiyan; Chen, Ling; Gao, Jinzhi (Frontiers in Pediatrics, 2022)
Food protein-induced enterocolitis syndrome (FPIES) is a type of non-immunoglobulin E (IgE)-mediated food allergy. However, in addition to vomiting and diarrhea, IgE-mediated skin or respiratory symptoms may be comorbidities in some patients with FPIES. We described four unusual cases of neonates with FPIES, whose clinical presentations were variable and misleading. All patients experienced vomiting, diarrhea or other gastrointestinal symptoms, and three of them developed IgE-mediated food allergy. Case 1 was admitted to the hospital with convulsions and then developed severe sepsis and necrotizing enterocolitis-like appearance. Case 2 was wrongly diagnosed with Stevens-Johnson syndrome due to a severe extravasation rash of the skin and mucous membranes and a systemic inflammatory response. There was unexplained cholestasis in case 3, which might be attributed to food allergy. Asymptomatic elevation of C-reactive protein was the only hint at early-stage FPIES in case 4. Moreover, there were increased serum food-specific IgG values in three of the above cases. After eliminating the offending food, all of the above clinical manifestations rapidly improved in the four cases; thus, we believe that the most correct diagnosis in the described four cases was FPIES. This case report series should further draw clinicians’ attention to FPIES with variable and atypical symptoms. The usefulness of IgG levels in identifying the presence of FPIES is uncertain.